Atypical location of primary cardiac lymphoma in the left heart with atypical clinical presentation: A case report and literature review - Qiang, Yongjia; Zeng, Kuan; Zhang, Bin; Guan, Ruicong; Liu, Yuqiang; Liu, Zhuxuan; Xu, Haohua; Zhang, Xinyi; Ren, Yanting; Deng, Baoping; Yang, Yanqi (Frontiers in Surgery, 2023)
Background Primary cardiac lymphoma (PCL) is a rare and aggressive cardiac tumor with very poor prognosis that occurs mostly in the right cardiac cavity. Early diagnosis and treatment may improve its prognosis. In the present report, we describe the diagnosis and treatment of a primary cardiac diffuse large B-cell lymphoma (PC-DLBCL) with atypical location and clinical presentation. Additionally, a literature review was conducted to summarize the current knowledge of the disease. Case Presentation A 71-year-old man visited his local hospital because of syncope, recurrent chest tightness, shortness of breath, palpitations, and profuse sweating for more than 20 days. Chest radiography revealed a mediastinal mass. Cardiac computed tomography (CT) showed multiple enlarged mediastinal lymph nodes. Transthoracic echocardiography (TTE) showed a cardiac mass in the posterior–inferior wall of the left atrium. He was then transferred to our hospital for positron emission tomography-CT (PET-CT) which showed active uptake of fluorodeoxyglucose both in the cardiac mass and in the multiple enlarged mediastinal lymph nodes. Biopsy of the enlarged mediastinal lymph nodes was carried out by using video-assisted thoracic surgery (VATS) technique, and pathological examination confirmed the subtype of PC-DLBCL, Stage IV, NCCN IPI 3. Therefore, the patient received a combination of chemotherapy and immunotherapy with R-CDOP (rituximab, cyclophosphamide, liposome doxorubicin, vincristine, and prednisone). After four courses of treatment in 4 months, the cardiac lymphoma and the enlarged mediastinal lymph nodes achieved complete remission with mild side effects of the chemotherapy. Conclusion Early diagnosis and a precise choice of chemotherapy and immunotherapy based on cardiac imaging and pathological examination may improve the prognosis of PC-DLBCL in an atypical location.